2018
DOI: 10.1111/nph.15046
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin antagonizes jasmonate‐induced defense against Meloidogyne graminicola in rice

Abstract: Gibberellin (GA) regulates various plant growth and developmental processes, but its role in pathogen attack, and especially nematode-plant interactions, still remains to be elucidated. An in-depth characterization of the role of GA in nematode infection was conducted using mutant lines of rice, chemical inhibitors, and phytohormone measurements. Our results showed that GA influences rice-Meloidogyne graminicola interactions in a concentration-dependent manner. Foliar spray of plants with a low concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 84 publications
(211 reference statements)
0
42
1
Order By: Relevance
“…Among the genes related to plant hormones, the expression of the two genes OsCPS4 (Os04g0178300) and OsKS4 (Os04g0179700) related to gibberellin synthesis was mostly induced by H. mucronata in the infected roots of Bawangbian (log 2 FC = 10.61) and Jiabali (log 2 FC = 9.73), respectively. In contrast with the observations from M. graminicola and rice interactions, gibberellin plays a dominant role over JA in determining the susceptibility to M. graminicola in rice [23]. It could be that gibberellin has important roles in the interaction between rice and H. mucronata.…”
Section: Resistance and Susceptible Host Response To H Mucronata Infcontrasting
confidence: 63%
See 1 more Smart Citation
“…Among the genes related to plant hormones, the expression of the two genes OsCPS4 (Os04g0178300) and OsKS4 (Os04g0179700) related to gibberellin synthesis was mostly induced by H. mucronata in the infected roots of Bawangbian (log 2 FC = 10.61) and Jiabali (log 2 FC = 9.73), respectively. In contrast with the observations from M. graminicola and rice interactions, gibberellin plays a dominant role over JA in determining the susceptibility to M. graminicola in rice [23]. It could be that gibberellin has important roles in the interaction between rice and H. mucronata.…”
Section: Resistance and Susceptible Host Response To H Mucronata Infcontrasting
confidence: 63%
“…and Table S4). Gibberellin plays important roles in the susceptibility of rice to M. graminicola infection . M. graminicola infection in rice induces strong transcriptional changes in the gibberellin (GA) biosynthesis ( GA20ox1 and GA20ox2 ) and signaling ( GID1L2 ) genes in galls (3 and 7 DAI) and giant cells (7 and 14 DAI) .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a phytochrome‐interacting factor ( PIF ) (c69497_c0) gene showed a higher expressed level in the susceptible genotype at all stages, contrast to two other PIF genes (c59912_c1 and c76228_c1). Previous studies indicated that GA antagonized JA‐induced defence against pathogen attack in rice (Siciliano, Carneiro, Spadaro, Garibaldi, & Gullino, ; Yimer et al, ). The functional divergence of those genes involved in GA signalling pathway may result in different response to RSD of the two genotypes.…”
Section: Resultsmentioning
confidence: 94%
“…simultaneously influence plant cell differentiation and modulate the defense responses to establish a successful infection via feeding cell formation (Gheysen & Mitchum, 2011;Ji et al, 2013). The plant hormones JA, ethylene, SA, ABA, brassinosteroids (BR), gibberellic acid (GA), and auxin are known to be involved in the interactions between plant and root-knot nematodes (Karczmarek et al, 2004;Nahar et al, 2011Nahar et al, , 2013Kyndt et al, 2017;Yimer et al, 2018;Gheysen & Mitchum, 2019). For instance, the JA-based defense pathway plays a vital role in rice defense against M. graminicola infection, whereas SA is also involved in defense but to a lesser extent than JA (Nahar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the JA-precursor cis-(+)-12-oxo-phytodienoic acid (cis-OPDA) acts as a signaling molecule in regulating Arabidopsis defense against M. hapla (Gleason et al, 2016). On the other hand, ABA, BR, and GA promote rice susceptibility to M. graminicola infection by interacting antagonistically with the JA pathway Kyndt et al, 2017;Yimer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%